Aplicação de ferramentas de nudges e sua influência nas decisões de investimentos no mercado de ações: um estudo em uma instituição financeira. - Pereira, Thiago Bandeira Lima (2021)
Objective: This work aimed to analyze the influence of nudges on investment decisions in shares, on customers of a large bank, who do not participate in the Brazilian stock market. The justification for this study is based mainly on the growth potential of the capital market in Brazil, coupled with the biases existing in investors and the existence of nudges in order to mitigate such impact. Design / methodology / approach: This work involves a combination of methodologies with quantitative and qualitative approaches, with an explanatory objective, with applications of qualitative and quantitative procedures. In methodological terms, the study is an applied research, using joint methods and the study was considered to be exploratory, since the sampling procedure was non-probabilistic. For data collection, a questionnaire with a 10-point ordinal scale was developed in the first phase. In the second phase, the questionnaire was developed in four parts, with different scales, qualified to capture from the respondents: the demographic profile, the importance of the nudges, the investment profiles and the types of bias heuristics. In the first phase, an analysis was made of the classification of nudges by type, as well as factorial analysis of them. In the second phase, the descriptive analysis and logistic regression of the nudges was performed. Results: Initially, it was possible to identify 25 tips and information released by brazilian capital Market regulatory entities, which were classified and validated as nudges. The nudges could be classified into 6 different factors and for the factors with the highest amount of nudges, nudges of Reminder and Alert were predominant. Through the second phase, it was found that nudges have the potential to influence investment decisions, including in individuals who showed bias and heuristics. Most respondents demonstrated an intention to invest, after receiving the nudges, with different results depending on the investment profiles and also according to each type of nudge, with a greater predominance of Remember and Alert nudges among those most selected by the respondents as influencers. Practical implications: The results obtained in this work shows nudges as tools to optimize decisions and will allow Banco B to define strategies with the objective of increasing the number of clients who invest in shares, increasing the investor base in this type of capital market asset. The Bank can use this tool adapting their use to the investment profiles defined by the Bank. Originality and contributions: This study innovates by making available low-cost tools that can be used by capital market participants, including regulatory entities and other financial institutions, in order to use the nudges of this work to encourage the number of people who invest in the stock market, with the potential to bring development, maturation and growth to the Brazilian capital market, with evident positive consequences for the entire economy of the country.